Analysing The Adoption Of Artificial Intelligence In Audit Practice - Baiq Wahyuni Damayanti; Bambang Bambang (UNIVED Press, 2024)
AI adoption until now has not been maximized by academics and audit practitioners due to many limitations, especially at Mataram University. This research then aims to find out the views of audit lecturers on AI adoption and how the level of AI adoption at Mataram University. This research is a descriptive qualitative research using subject data types and primary data sources. The data collection technique used was a structured interview with audit lecturers at Mataram University. Data analysis techniques consist of data reduction, data presentation, and conclusions which then uses data triangulation to increase data validity. The results showed that the adoption of AI in the view of audit lecturers at Mataram University is very important with regard to the progress of the times and expectations for quality audits. Then related to the level of AI adoption in audit practices at the University of Mataram, it was found that there has not been massive adoption, so in the future it is expected to be adopted selectively in order to produce quality audit processes and results and go hand in hand with technological advances. The recommendations offered then are HR training and commitment and consistency in AI adoption in audit practices at Mataram University.